On the Relationship Between Interest Rates and Economic Growth: Theory and Empirical Evidence - Carl Christian von Weizsäcker; Hagen Krämer (Wirtschaftsdienst)
Abstract In the August 2020 issue of Wirtschaftsdienst Hans-Werner Sinn, Peter Bofinger and Eckhard Hein made critical comments on our book “Sparen und Investieren im 21. Jahrhundert — Die große Divergenz” (Saving and Investing in the 21st Century — The Great Divergence). In this article, we respond to their critique. In particular, we deal with the controversial phenomenon of dynamic inefficiency, with the criticisms of our concept of implicit public debt, the interpretation of economic paradigms, and the allegation of having neglected monetary aspects in our theory.